2012
DOI: 10.1039/c2cp41694h
|View full text |Cite
|
Sign up to set email alerts
|

A novel low compressible and superhard carbon nitride: Body-centered tetragonal CN2

Abstract: A novel body-centered tetragonal CN(2) (4 units per cell), named as bct-CN(2), has been predicted here using our newly developed particle swarm optimization algorithm for crystal structure prediction. Bct-CN(2) is energetically much superior (3.022 eV per f.u.) to previously proposed pyrite structure and stable against decomposition into a mixture of diamond + N(2) or 1/3(C(3)N(4) + N(2)) above 45.4 GPa. No imaginary phonon frequencies in the whole Brillouin zone indicate bct-CN(2) is dynamically stable. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 75 publications
8
68
1
Order By: Relevance
“…From Table 1, we find unusually high incompressibility along c-direction for P4 2 /m-CN, as demonstrated by the extremely large C 33 value (1156 GPa), which is slightly larger than the experimental data of diamond (C 33 : 1076 GPa). 43 This value is comparable to those of known potential superhard materials (β-C 3 N 4 (1053 GPa), 12 bct-C 4 (1189.9 GPa), 44 and Z-carbon (1184.5 GPa) 44 ) suggesting that the c-axial direction of P4 2 /m-CN is very stiff. The polycrystalline bulk modulus B, shear modulus G, Young's modulus E, Poisson's ratio v, and G/B of P4 2 /m-CN are also shown in Table 1.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…From Table 1, we find unusually high incompressibility along c-direction for P4 2 /m-CN, as demonstrated by the extremely large C 33 value (1156 GPa), which is slightly larger than the experimental data of diamond (C 33 : 1076 GPa). 43 This value is comparable to those of known potential superhard materials (β-C 3 N 4 (1053 GPa), 12 bct-C 4 (1189.9 GPa), 44 and Z-carbon (1184.5 GPa) 44 ) suggesting that the c-axial direction of P4 2 /m-CN is very stiff. The polycrystalline bulk modulus B, shear modulus G, Young's modulus E, Poisson's ratio v, and G/B of P4 2 /m-CN are also shown in Table 1.…”
Section: Resultssupporting
confidence: 81%
“…As is known for carbon nitrides, four-coordinated carbon and three-coordinated nitrogen leads to high bulk modulus and large hardness values. 12 At 0 GPa, the calculated lattice parameters of P4 2 /m-CN are a = b = 4.666 Å and c = 2.373 Å in a unit cell in which two nonequivalent atoms C and N occupy the Wyckoff 4j (0.3323, 0.9737, 0.0) and 4j (0.8136, 0.7391, 0.0) sites, respectively. In more detail, the C−C bond length in the P4 2 /m phase is 1.584 Å at 0 GPa, slightly longer than that in diamond (1.535 Å) but shorter than that in Pnnm phase (1.606 Å).…”
Section: Resultsmentioning
confidence: 99%
“…The ideal tensile strength in a specified direction is microscopically determined by bond strength and breaking nature under strain. 47 Fig. 5 shows the ideal tensile strength of TBBC-carbon along several high-symmetry directions.…”
Section: Resultsmentioning
confidence: 99%
“…In light of the extensive applications of c -BN as superhard material, boron nitride compounds, such as Z -BN, Pbca -BN, w -BN, O -BN, and C 222 1 -B 3 N 5 , have been found to be superhard [1,2,3,4,5,6]. Except boron nitrides, carbon nitrides are also expected to be potential superhard materials [7,8,9,10,11,12,13,14,15]. Since the prediction of hexagonal β -C 3 N 4 with extraordinary hardness, extensive experimental, and theoretical investigations have been carried out to search for new C–N materials with novel properties.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several different crystal structure prediction technique-based algorithms have been the most prevalent strategies to explore and predict new material structures. Using the swarm optimization technique, Li et al [13] found a novel low compressible and superhard bct -CN 2 phase. Zhang et al predicted that the stable CN is P 4 2 / m phase [11].…”
Section: Introductionmentioning
confidence: 99%